Development of Carrot Nutraceutical Products as an Alternative Supplement for the Prevention of Nutritional Diseases - Riaz, Nadia; Yousaf, Zubaida; Yasmin, Zarina; Munawar, Muneeb; Younas, Afifa; Rashid, Madiha; Aftab, Arusa; Shamsheer, Bushra; Yasin, Hamna; Najeebullah, Muhammad; Simon, Philipp W. (Frontiers in Nutrition, 2022)
Nutraceuticals can be an alternative supplement to overcome the nutrition deficiency for a healthy lifestyle. They could also play a key role in disease management. To develop carrot nutraceutical products, 64 genotypes from four different continents were assessed by morpho-nutrition variables. Genetic variability, heritability, strength and direction of association, direct and indirect effects of physiochemical and nutritional traits on β-carotenoid were evaluated. Core diameter, foliage weight, root weight and shoulder weight showed significant effects on beta carotenoid accumulation. Principal component analysis for physiochemical and nutritional assessment divided these genotypes into two distinctive groups, Eastern carrots and Western carrots. Calories (33.0), moisture (24.4) and protein (0.12) directly affected β-carotene. However, vitamin C (-0.214), carbohydrates (-8.5) and fat (-0.08) affects negatively. Five genotypes (T-29, PI 634658, PI 288765, PI 164798 and Ames 25043) with highest beta carotenoid contents were selected for making three nutraceutical supplements (carrot-orange mix juice, carrot jam and carrot candies). These nutraceutical supplements retained high β-carotenoid content coupled with antioxidant properties. Carrot jam (6.5mg/100g) and carrot candies (4.8mg/100gm) showed greater concentrations of β-carotene than carrot-orange mix juice (1.017). Carrot jam presented gradual increase in antioxidant activity with highest in T-29 (39%) followed by PI 634658 (37%), PI 164798 (36.5%) and Ames 25043 (36%) and PI 288765 (35.5%). These nutraceutical products with 4 -6.5mg/100gm beta carotenoid content, higher than the USDA recommended dietary intake of 3-6mg β carotene/day can be recommended for daily use to lower the risk of chronic disease.